Vitamin D deficiency and female infertility: A mechanism review examining the role of vitamin D in ovulatory dysfunction as a symptom of polycystic ovary syndrome. (June 2022) - Berry, Sinéad; Seidler, Karin; Neil, James
Abstract: Around one billion people worldwide are understood to have sub-optimal levels of vitamin D. Polycystic ovary syndrome (PCOS) is reportedly a primary reason for female infertility. The main objective of this research was to understand the mechanistic role of vitamin D in the pathogenesis of female infertility in PCOS, specifically in relation to ovarian follicle development. In addition, the impact of vitamin D deficiency on oxidative stress and hormone production central to folliculogenesis was explored. The efficacy of vitamin D supplementation as an intervention to ameliorate ovulatory dysfunction in individuals with PCOS was evaluated. The systematic search strategy included three stages of search with a critical appraisal of the accepted papers: 1) other review papers; 2) primary mechanistic animal, in vitro and human studies; 3) primary intervention studies. In total, 80 papers were examined in detail and results analysed and evaluated. Mechanistic evidence indicated an association between vitamin D deficiency and impaired ovulatory function. Sub-optimal vitamin D levels were implicated in disrupted reproductive hormone balance, including overproduction of anti-mullerian hormone (AMH); accumulation of pro-inflammatory Advanced Glycation End Products (AGEs) and formation of Reactive Oxygen Species (ROS) in ovarian tissue, leading to abnormal folliculogenesis. Human intervention studies demonstrated the capability of vitamin D supplementation for restoring sufficient serum calcidiol (25(OH)D) levels in deficient individuals. Furthermore, the anti-inflammatory benefit of vitamin D was illustrated in studies examining the impact on oxidative stress. Co-supplementation with calcium was shown to benefit follicle growth; oxidative stress reduced with calcium, omega-3 fatty acid or probiotic co-supplementation. Graphical Abstract: ga1 Highlights: Vitamin D plays a role in pathophysiological mechanisms of infertility in PCOS. Vitamin D deficiency is linked to dysregulation of hormones and folliculogenesis. Advanced Glycation End Products are implicated in anovulation in PCOS. A suitable reproductive environment may be supported by vitamin D sufficiency. Irregular follicle development may be reversed with vitamin D supplementation.